First records of two Triplax species (Coleoptera, Erotylidae) from Kazakhstan - Izbasar I. Temreshev (Acta Biologica Sibirica, 2024)
Pleasing fungus beetles Triplax aenea (Schaller, 1783) and T. melanocephala (Latreille, 1804) from the family Erotylidae are firstly recorded from Kazakhstan. A new key to known species of the genus Triplax from Kazakhstan is given. The finds of T. aenea from South-East Kazakhstan are currently new record for this species for Central Asia. The finds of T. melanocephala from South-East Kazakhstan are currently the easthernmost localities for this species and new record for Central Asia. Dryad's saddle mushroom Cerioporus squamosus, big sheath mushroom Volvopluteus gloiocephalus, Rhodofomes roseus and milk-caps mushroom Lactarius badiosanguineus are firstly recorded from Kazakhstan for T. aenea; fungi from family Agaricaceae – field mushroom A. campestris and Prince mushroom A. augustus for T. melanocephala.